An assessment of “Communication strategies used by World Vision to alleviate poverty in Nkayi community” 2014-2015. - Ndou, Vigelence (Midlands State University, 2017)
The study focused on the communication strategies used by World Vision to alleviate poverty in Nkayi community from 2014 to date. Communication is essential for every organisation to survive in its operational environment and to create a rapport and mutually understanding with the surrounding community. The study also focuses on identifying the communication strategies that are used by World to alleviate poverty. The study had to assess the effectiveness of communication strategies used by World Vision and the extent to which the community of Zhende and Mantoni in Nkayi expressed satisfaction. The study was influenced by two way communication, stakeholders salience and open system theory. Furthermore, the study explored qualitative and quantitative research design to attain results that are closer to validity and reality. Interviews, questionnaires and participation observation were used to tape information from the targeted population who are World Vision workers from various departments and community members in Mantoni and Zhende. The study seeks to establish the importance of communication by non governmental organisation like World Vision, and the extent to which poverty can be reduced.